Moscow Information and Technological University – Moscow Architecture and Construction Institute Is an Innovative Architectural School - Bulgakova, Elena (project baikal, 2017)
The article presents the experience of Moscow Information and Technological University – Moscow Architecture and Construction Institute (MITU MACI) in creating an advanced model of architecture school focused on an innovative approach in education to intensify the educational process. The article touches upon “impermeability” of the architectural profession and the possible ways out with the help of introduction of new forms of education and an interdisciplinary approach.